TLR3 Signaling Promotes the Induction of Unique Human BDCA-3 Dendritic Cell Populations - Colletti, Nicholas J.; Liu, Hong; Gower, Adam C.; Alekseyev, Yuriy O.; Arendt, Christopher W.; Shaw, Michael H. (Frontiers in Immunology, 2016)
Conventional and plasmacytoid dendritic cells (cDCs and pDCs) are the two populations of DCs that can be readily identified in human blood. Conventional DCs have been subdivided into CD1c+, or blood dendritic cells antigen (BDCA) 1 and CD141+, or BDCA-3, DCs, each having both unique gene expression profiles and functions. BDCA-3 DCs express high levels of toll-like receptor (TLR) 3 and upon stimulation with Poly:IC secrete IFN-β, CXCL10, and IL-12p70. In this article, we show that activation of human BDCA-3 DCs with Poly:IC induces the expression of activation markers (CD40, CD80, and CD86) and immunoglobulin-like transcript (ILT) 3 and 4. This Poly:IC stimulation results in four populations identifiable by flow cytometry based on their expression of ILT3 and ILT4. We focused our efforts on profiling the ILT4- and ILT4+ DCs. These ILT-expressing BDCA3 populations exhibit similar levels of activation as measured by CD40, CD80, and CD86; however they exhibit differential cytokine secretion profiles, unique gene signatures, and vary in their ability to prime allogenic naïve T cells. Taken together, these data illustrate that within a pool of BDCA-3 DCs there are cells poised to respond differently to a given input stimulus with unique output of immune functions.